Split-based elevational localization of photoacoustic guidewire tip by 1D array probe using spatial impulse response - Tanaka, Tomohiko; Imai, Ryo; Takeshima, Hirozumi (Physics in medicine & biology, 2024)
Objective . Photoacoustic emitters on the tip of a therapeutic device have been intensively studied for echo-guided intervention purposes. In this study, a novel method for localizing the guidewire tip emitter in the elevation direction using a 1D array probe is proposed to resolve the issue of the tip potentially deviating from the ultrasound-imaged plane. Approach . Our method uses the ‘interference split’ that appears when the emitter is off-plane. Here, a point source from the emitter splits into two points in images. Based on the split, ‘split-based elevation localization (SEL)’ is introduced to estimate the absolute elevation position of the emitter. Additionally, ‘Signed SEL’ incorporates an asymmetric feature into the 1D probe to obtain the sign of the elevation localization. An attenuative coupler is attached to the half side of the probe to control the interference split. In SEL and Signed SEL, we propose a modeled split matching (MSM) algorithm to localize the tip position. MSM performs pattern matching of a measured split waveform with modeled split waveforms corresponding to all emitter positions in a region of interest. The modeled waveforms are precalculated using the spatial impulse response. The proposed method is numerically and experimentally validated. Main results . Numerical simulations for time-domain wave propagation clearly demonstrated the interference split phenomena. In the experimental validation with a vessel-mimicking phantom, the proposed methods successfully estimated the elevation positions, y b . SEL exhibited a root-mean-squared error (RMSE) of 2.0 mm for the range of 0 mm ≤ y b ≤ 30 mm, while Signed SEL estimated the absolute position with an RMSE of 2.4 mm and the sign with an accuracy of 80.8% for the range of −30 mm ≤ y b ≤ 30 mm. Significance. These results suggest that the proposed method could provide approximate tip positions and help sonographers track it by fanning the probe.